Current Research On Pharmacological and Toxicological of Croton tiglium Linn. - Poowanna, Ronnachai; Pakdee, Naruwat; Nualkaew, Somsak (Kalasin University Journal of Science Technology and Innovation, 2024)
Croton tiglium L., commonly known as Purging Croton and classified under the Euphorbiaceae family, has been traditionally used in Thai medicine as a potent purgative to treat colic, asthma, cough, phlegm, lymphatic disorders, cathartic, blood disorders, and parasitic infections. The seeds of Croton tiglium are incorporated in various formulations for treating symptoms resembling cancer. The chemical composition of the seeds includes oil (30.00-56.00%), carbohydrates (16.15%), proteins (16.00%), fibers (8.25%), and ash (3.60%). Key chemical constituents of the seeds are phorbol esters such as Phorbol-12-myristate-13-acetate, along with alkaloids, fatty acids, and amino acids. Phorbol esters exhibit a range of pharmacological activities, including antifungal, antiviral, antibacterial, laxative, vaccine adjuvant and anti-inflammatory properties. Notably, they demonstrate significant anticancer properties, effectively inhibiting the growth of cancer cells, including liver cancer, leukemia, lung cancer, prostate cancer, breast cancer, and gastric cancer. The inhibitory concentrations (IC50) of these compounds are typically within the micromolar range. Despite its medicinal potential, the presence of phorbol-12-myristate-13-acetate (PMA) poses a major drawback due to its toxicity and role as a tumor promoter. Various methods have been developed to reduce the toxicity of Croton tiglium seeds, effectively lowering PMA levels. However, comprehensive data on the reduction of carcinogenic promotion activity is still lacking. If these detoxification methods can be proven to effectively reduce both PMA levels and its carcinogenic promotion activity, Croton tiglium could emerge as a promising herbal alternative for cancer treatment. Recent discoveries highlight the potential of phorbol esters as Protein kinase C (PKC) activators that inhibit specific PKC isoforms linked to cancer inhibition. The development of cancer therapies targeting specific PKC isoforms is currently a significant area of interest.